Nilai Kearifan Lokal Dalam Pemberdayaan Perempuan Pada Songket Pandai Sikek - Trina Febriani; Wibi Wijaya; Felia Siska (Bakaba, 2021)
This study discusses the value of local wisdom in women's empowerment in Songket Pandai Sikek. Songket woven fabric craftsmen who still use the traditional method have decreased significantly, because there are non-machine looms or ATBMs that can produce songket for a maximum of 4 days, which previously took 40 days, while the purpose of this research is to describe the value of local wisdom. in Women's Empowerment in Songket clever Sikek in Jorong Tanjuang Nagari Pandai Sikek District X Koto Tanah Datar. The theory used is the theory of rational choice by James S. Coleman. Then the research method used a qualitative approach with descriptive type, the informants consisted of 27 people who were determined by purposive sampling. The types of data are primary and secondary data. Data were collected through observation, interviews and document research. Data analysis uses the Miles and Huberman model, namely data collection, data reduction, data presentation and conclusions. The results of this study indicate that local wisdom can be seen from the first: the motifs used in the clever sikek songket weaving process using the theme of the surrounding nature, second: The ability of the craftsmen to be open to various changes is one way to develop the art of Pandai Sikek weaving.